1997
DOI: 10.1155/mbd.1997.273
|View full text |Cite
|
Sign up to set email alerts
|

Considerations in Platinum and Gold Drug Design and the Synthesis of Chloro(2,3‐Diphenyl‐1,3,4‐Thiadiazolium‐5‐Thiolato‐Sexo)Gold(I): The First Gold Meso‐Ionic Complex of Its Kind

Abstract: It is evident that the chemistry of platinum is in a more advanced state than that of gold, mainly due to the success of the former in several anti-cancer drugs. With a view to finding possible, new candidates with chemotherapeutic potential, the use of sulphur-donor ligands bonded to platinum and gold is discussed herein in an attempt to promote the need to investigate similar ligands. Chloro(2,3-diphenyl-l,3,4-thiadiazolium-5-thiolato-Sexo)gold(I) has been synthesised using a standard reaction, whereby Au(ll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In this last field, the compounds under investigation include a major collection of the type R 3 PAuL, in which the gold atom is coordinated to a phosphine ligand and L is an O- [26,27], N- [28,29], Cl- [30] or S- [29,[31][32][33][34][35] 2 ], Na 3 [Au(mna) 2 ] (H 2 mna 02-mercaptonicotinic acid) [13] and the cationic complexes [Au(L) 2 ](NO 3 ) 3 (L01-[2-(acridin-9-ylamino)ethyl]-1,3-dimethylthiourea) [34]. For the latter ligand, compounds of the type [Au(L)]Br, [Au(L)] SCN and [Au(L)]Cl were also prepared [34] and the coexistence of an S-donor ligand and a Cl ligand was also described for [LAuCl] (where L 02,3-diphenyl-1,3,4-thiadiazolium-5-thiolato-S exo ) [36].…”
Section: (L)] [Hq][ag(l)] (Hq0diisopropylammonium)mentioning
confidence: 99%
“…In this last field, the compounds under investigation include a major collection of the type R 3 PAuL, in which the gold atom is coordinated to a phosphine ligand and L is an O- [26,27], N- [28,29], Cl- [30] or S- [29,[31][32][33][34][35] 2 ], Na 3 [Au(mna) 2 ] (H 2 mna 02-mercaptonicotinic acid) [13] and the cationic complexes [Au(L) 2 ](NO 3 ) 3 (L01-[2-(acridin-9-ylamino)ethyl]-1,3-dimethylthiourea) [34]. For the latter ligand, compounds of the type [Au(L)]Br, [Au(L)] SCN and [Au(L)]Cl were also prepared [34] and the coexistence of an S-donor ligand and a Cl ligand was also described for [LAuCl] (where L 02,3-diphenyl-1,3,4-thiadiazolium-5-thiolato-S exo ) [36].…”
Section: (L)] [Hq][ag(l)] (Hq0diisopropylammonium)mentioning
confidence: 99%
“…[15][16][17][18][19] For instance, the drugs like Auranofin, Solganol and Myocrisin have frequently been used for the treatment of rheumatoid arthritis. [20][21][22][23][24] Interestingly, the extensive cell-based (in vitro) and animal (in vivo) studies have revealed the potent anticancer activities of diverse classes of gold(I) and gold(III) complexes with a wide range of ligands against a panel of human cancer cell lines. [25][26][27] An enormous number of bridged di-gold(I) complexes, preferably existing in a linear 2-coordinate configuration like [ClAu(P-P)AuCl] (where P-P is a bisphosphine), are more effective than free ligands and exhibit a broad range of anticancer activities.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, there was substantial interest in the coordination chemistry of Au (I) complexes showing biological activity with potential medicinal applications. For instance, the currently used drugs like Auranofin, Solganol and Myocrisin are Au(I)-S complexes [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%